Simulation of robot arm system control using fuzzy logic - Syarifa Fitria; Sariman Sariman; Zainuddin Nawawi; Rizda Fitri Kurnia; Dwirina Yuniarti; Tresna Dewi (Control and Computational Intelligent System (CoCIS) Research Group, 2024)
This study explains a robot arm system control simulation using a fuzzy logic controller. The robot arm is a nonlinear system and is not easily controlled using a conventional control system since the mathematical model of the system is not easy to obtain. Considering these problems, this final project presents a simulation of a fuzzy logic controller on a robot arm system. The aim of this control is to move the robot arm at an angular speed thus the robot gets the desired torque or the right position. Determining fuzzy rules greatly influences system stability. This control network produces output in the form of torque while the robot arm system calculates the next torque from the robot. The best output results were found on the triangular curve at response 2 because of the difference in values 0.01 on the final angle obtained.